Memory of trees : a daughter's story of a family farm - Marty, Gayla (University of Minnesota Press, 2010)
Memory of Trees is a multigenerational story of Gayla Marty's family farm near Rush City, Minnesota. Cleared from woodlands by her great-grandfather Jacob in the 1880s, the farm passed to her father, Gordon, and his brother, Gaylon. Hewing to a conservative Swedish Baptist faith, the two brothers worked the farm, raising their families in side-by-side houses. As the years go by, the families growand slowly grow apart. Uncle Gaylon, more doctrinaire in his faith, rails against the permissiveness of Gayla's parents. Financial tensions arise as well when the farm economy weakens and none of the.